2009
DOI: 10.48550/arxiv.0905.1655
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On the Infinitude of Some Special Kinds of Primes

Shaohua Zhang

Abstract: The aim of this paper is to try to establish a generic model for the problem that several multivariable number-theoretic functions represent simultaneously primes for infinitely many integral points. More concretely, we introduced briefly the research background-the history and current situation-from Euclid's second theorem to Green-Tao theorem. We analyzed some equivalent necessary conditions that irreducible univariable polynomials with integral coefficients represent infinitely many primes, found new necess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The proofs of these propositions can be obtained from the results of Theorems 2,4,5,6,and 8,respectively. As there are no solutions for Eq. 12 where (π‘₯, 𝑦, 𝑝)∈{(𝐿 𝑖 , 𝐿 𝑗 , 𝐿 π‘˜ ),(𝑄 𝑖 , 𝑄 𝑗 , 𝑄 π‘˜ ), (𝑀 𝑖 , 𝑀 𝑗 , 𝑀 π‘˜ ), (𝑁 𝑖 , 𝑁 𝑗 , 𝑁 π‘˜ ), (𝐸 𝑖 , 𝐸 𝑗 , 𝐸 π‘˜ )}, it can be easily concluded that Eq.…”
Section: Proof Of Propositions 2456 Andmentioning
confidence: 99%
See 1 more Smart Citation
“…The proofs of these propositions can be obtained from the results of Theorems 2,4,5,6,and 8,respectively. As there are no solutions for Eq. 12 where (π‘₯, 𝑦, 𝑝)∈{(𝐿 𝑖 , 𝐿 𝑗 , 𝐿 π‘˜ ),(𝑄 𝑖 , 𝑄 𝑗 , 𝑄 π‘˜ ), (𝑀 𝑖 , 𝑀 𝑗 , 𝑀 π‘˜ ), (𝑁 𝑖 , 𝑁 𝑗 , 𝑁 π‘˜ ), (𝐸 𝑖 , 𝐸 𝑗 , 𝐸 π‘˜ )}, it can be easily concluded that Eq.…”
Section: Proof Of Propositions 2456 Andmentioning
confidence: 99%
“…Furthermore, Dirichlet proved that there are an infinite number of primes of the form 𝑝 = π‘Žπ‘˜ + 𝑏 if 𝑔𝑐𝑑(π‘Ž, 𝑏) = 1, where π‘Ž and 𝑏 are integers, see e.g. 6 . Indeed, this latter result demonstrates that there are an infinite number of primes of the form 𝑝 = π‘₯ 2 + 𝑦 2 .…”
Section: Introductionmentioning
confidence: 99%